2018
DOI: 10.1039/c7ob03079g
|View full text |Cite
|
Sign up to set email alerts
|

Grignard-mediated rearrangement of trifluoroacetyl from dihydroisoquinoline enamides to afford tertiary trifluoromethylcarbinols

Abstract: Treatment of the trifluoroacetyl enamides of dihydroisoquinolines 2 with diverse Grignard reagents afforded tertiary trifluoromethyl-carbinols 4 by facilitating the addition of tertiary carbinols to the β-carbon of enamides 2. Based on the confirmed formation of vinylogous amides 3, the transformation likely proceeds via unique acyl group rearrangement to the β-carbon of the enamide and subsequent nucleophilic addition of the Grignard reagent. Given the synthetic utility and novelty of this reaction, this work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…As shown in Entry 3, the first attempt (TFAA, TFA, Fe), [28] wherein the conditions identical to Entry 2 were employed, was unsuccessful. However, the reaction with Lewis acid (TMSCl) [29] provided the desired TFA enamide 27 b in 23 % yield (Entry 4). The yield was improved to 63 % by using TESCl (Entry 5).…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Entry 3, the first attempt (TFAA, TFA, Fe), [28] wherein the conditions identical to Entry 2 were employed, was unsuccessful. However, the reaction with Lewis acid (TMSCl) [29] provided the desired TFA enamide 27 b in 23 % yield (Entry 4). The yield was improved to 63 % by using TESCl (Entry 5).…”
Section: Resultsmentioning
confidence: 99%
“…Energy dispersive X‐ray spectrometer (EDS) data were obtained using Bruker Quantax 200 EDS. DHIQs 1a‐e were prepared with reported methods …”
Section: Methodsmentioning
confidence: 99%
“…DHIQs 1a-e were prepared with reported methods. 35 General Procedure for the Preparation of 3. To a solution of DHIQ 1a (100 mg, 0.571 mmol, 1.0 equiv) in Table 4.…”
Section: Experimental General Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, significant advances in cascade reactions involving Grignard reagent-mediated rearrangements have been reported. [22][23][24][25][26] In addition, nucleophilic addition of Grignard reagents to esters is one of the methods for the synthesis of tertiary alcohols. Initially, Zwahlen et al 27 reported a nucleophilic/rearrangement/nucleophilic addition cascade between a Grignard reagent and an enol lactone to afford a 1,3-diol compound.…”
Section: Introductionmentioning
confidence: 99%